Effect of regular exercise on ocular inflammation and mitochondrial biogenesis in experimental Alzheimer’s disease model: Exercise and ocular health in Alzheimer’s disease - Okudan, Suleyman; Sezer, Tuğba; Tınkır Kayırbatmaz, Emine; Belviranli, Muaz; Okudan, Nilsel (Cellular and Molecular Biology, 2025)
This study investigates the effects of regular exercise on inflammation and mitochondrial biogenesis in the eye using a controlled experimental Alzheimer’s disease (AD) model. Twenty-four male Wistar rats were divided into four groups: control, Alzheimer, exercise, and Alzheimer with exercise. Molecular markers, including Nuclear Factor Kappa B (NF-κB), Fibronectin Type III Domain-Containing Protein 5 (FNDC5), Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-Alpha (PGC-1α), Sirtuin 1 (SIRT1) were analyzed through real-time quantitative reverse transcription-polymerase chain reaction (RT-PCR) Matrix Metalloproteinase 2 (MMP-2), and Interleukin-1 Beta (IL-1β) were analyzed enzyme-linked immunosorbent assay (ELISA) to evaluate exercise-induced changes in inflammation and mitochondrial function. NF-κB levels were significantly elevated in the Alzheimer group, reflecting neuroinflammation, while exercise partially mitigated these effects. Exercise increased FNDC5, PGC-1α, and SIRT1 levels, suggesting a role in promoting neuroprotection and mitochondrial biogenesis. However, MMP-2 and IL-1β effects were primarily observed at the gene expression level, without substantial changes in protein levels. The use of an Alzheimer-specific model reduced confounding factors, such as age-related pathologies, providing a clearer perspective on Alzheimer-associated ocular changes. These findings highlight the potential of exercise in modulating key molecular pathways involved in AD.